Perspectives of military-affiliated women on lethal means safety: A systematic review - Melissa A. Litschi; Megan Lafferty; Amy Riegelman; Steven L. Lancaster; David J. Linkh (PLoS ONE, 2026)
Background Women are the fastest-growing military cohort, with suicide rates rising faster than among veteran men and civilian women. Lethal means include firearms, used more often than by civilian women, and non-firearm methods like poisoning, used more than by veteran men. Despite these trends, most lethal means research is gender-neutral, and clinical guidance lacks gender-informed strategies. Objectives To synthesize literature on military-affiliated women’s perspectives on lethal means safety and how it should be addressed in suicide prevention conversations. Design Qualitative systematic review. Data sources APA PsycINFO via Ovid, Ovid MEDLINE ALL, select government and non-profit websites, and citation searching through December 2024. Methods Screening occurred in two stages (title/abstract and full text), with 30% of records double-screened. Quality appraisal was conducted using the Critical Appraisal Skill Programme (CASP), Consolidated Criteria for Reporting Qualitative Research (COREQ) Checklist, and Mixed-Methods Appraisal Tool (MMAT). Qualitative and quantitative data fragments were extracted and organized into domains on ownership, access, and means safety interventions. Thematic synthesis used an inductive coding approach. The protocol was published on OSF ( https://doi.org/10.17605/OSF.IO/Z8DJH ). Results Six of the seven articles included perspectives of VHA-enrolled women veterans on firearms or firearm safety counseling, two included active duty women. Three themes on firearm ownership and access emerged, highlighting variations in: understandings of safety surrounding firearms, the impact of military service and identity on firearm beliefs, and the role of spouses/partners in household firearm access. Three themes relating to lethal means safety counseling were identified: general acceptability of interventions, trust as a critical element of means safety conversations, and spouses as stakeholders in means safety conversations. Conclusions Lethal means safety counseling for military-affiliated women must be trauma-sensitive and gender-informed. Future research must expand beyond VA contexts and examine the impact and feasibility of engaging spouses in safety interventions.